General design approach and practical realization of decoupling matrices for parallel transmission coils. Issue 1 (31st July 2015) - Mahmood, Zohaib; McDaniel, Patrick; Guérin, Bastien; Keil, Boris; Vester, Markus; Adalsteinsson, Elfar; Wald, Lawrence L.; Daniel, Luca
Abstract : Purpose: In a coupled parallel transmit (pTx) array, the power delivered to a channel is partially distributed to other channels because of coupling. This power is dissipated in circulators resulting in a significant reduction in power efficiency. In this study, a technique for designing robust decoupling matrices interfaced between the RF amplifiers and the coils is proposed. The decoupling matrices ensure that most forward power is delivered to the load without loss of encoding capabilities of the pTx array. Theory and Methods: The decoupling condition requires that the impedance matrix seen by the power amplifiers is a diagonal matrix whose entries match the characteristic impedance of the power amplifiers. In this work, the impedance matrix of the coupled coils is diagonalized by a successive multiplication by its eigenvectors. A general design procedure and software are developed to generate automatically the hardware that implements diagonalization using passive components. Results: The general design method is demonstrated by decoupling two example parallel transmit arrays. Our decoupling matrices achieve better than −20 db decoupling in both cases. Conclusion: A robust framework for designing decoupling matrices for pTx arrays is presented and validated. The proposed decoupling strategy theoretically scales to any arbitrary number of channels. Magn Reson Med 76:329–339, 2016. © 2015 Wiley Periodicals, Inc.